Reservoir Quality Assessment Based on The Occurrence of Burial Diagenesis: Sandstone Case Study From Tanjung Formation, Barito Basin, South Kalimantan - Rosmalia Dita Nugraheni; Eko Widianto (Penerbitan Universitas Trisakti, 2021)
Barito Basin is known as one of hydrocarbon producing basin which is located in the Southeast Kalimantan. One of its prolific reservoir comes from sandstone facies of Tanjung Formation in the Paleo-Oligocene time. The sandstone undergone diagenesis, subsequently after deposition due to burial process. Burial diagenesis promotes further compaction, cementation and alteration which affect the reservoir quality. This study aims to assess the reservoir quality and its sensitivity against the diagenesis products. Research method was carried out by examine the core samples and scrutiny laboratory observation, such as Scanning Electron Microscope (SEM). X-ray Diffraction (XRD), porosity, permeability, grain density measurement and surface gamma-ray. The results show that the amount and type of alteration is vary by depth, age and lithofacies. Sandstones of sublitharenites and litharenites were buried to depths of 848.29 – 849.80 m and contained significant amounts of authigenic grain-coating and pore-lining clay as well as pore-filling zeolite cements. However, the underlying sandstones from 969.19 – 970.14 m depths exhibit less extensive alteration. In the early burial process, the reservoir quality is modified by the formation of secondary dissolution pores and minerals as a result of silicate dissolution during shallow burial diagenesis. The subsequent burial has reduced the pore spaces through mechanical compaction and cementtion. This study certainly valuable addition to our understanding about reservoir quality in correspond to the burial diagenesis.